Characterization of a novel chicken heat shock transcription factor, heat shock factor 3, suggests a new regulatory pathway. - Nakai, A (1993)
We have cloned three avian heat shock transcription factor (HSF) genes corresponding to a novel factor, HSF3, and the avian homologs of mammalian HSF1 and HSF2. The predicted amino acid sequence of HSF3 is approximately 40% related to the sequence of HSF1 and HSF2. The sequences for all three factors exhibit extensive identify in the DNA binding motifs and the heptad repeats of hydrophobic amino acids which are common to all eukaryotic HSFs. Despite these overall similarities, each avian HSF exhibits distinct DNA binding properties. HSF2 when expressed in vitro binds constitutively to the heat shock element promoter sequence, whereas neither HSF1 nor HSF3 expressed in vitro binds to DNA. HSF1 DNA binding is induced upon heat shock or treatment with nonionic detergents, whereas the DNA binding properties of HSF3 are not induced by these conditions in vitro. These results suggest that HSF3 activation may involve an induction pathway distinct from the traditional forms of heat shock gene induction. HSF3 DNA binding activity, however, is obtained when the carboxyl-terminal region including the distal heptad repeat is deleted, indicating the presence of negative cis-regulatory sequences. The HSF3 message, like HSF1 and HSF2 messages, is coexpressed during development and in most tissues, which suggests a general role for the regulatory pathway involving HSF3.